Online impulse buying: who had suggested you to buy on instagram - Assadam, Elvina (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
Since Instagram become phenomenon in this world and become new segment in business called Instagram commerce (Ig-commerce), this study aimed to know how peer communication and usage intensity trigger urge to buy impulsively and online impulse buying by following the stimulus organism response (SOR) paradigm. Data was collected by online survey from 180 customers who ever brought at Instagram more than 3 times and analyzed using partial least square (PLS). The result showed that there is significant effect of usage intensity and urge to buy impulsively of online impulse buying, but interestingly, we found that there is no direct effect of peer communication of online impulse buying; while indirect there is significant effect of online impulse buying.Â The research finding can contribute well to bosh the theorist as well as the practice.